2011
DOI: 10.1007/7854_2010_112
|View full text |Cite
|
Sign up to set email alerts
|

The Pig as a Model Animal for Studying Cognition and Neurobehavioral Disorders

Abstract: In experimental animal research, a short phylogenetic distance, i.e., high resemblance between the model species and the species to be modeled is expected to increase the relevance and generalizability of results obtained in the model species. The (mini)pig shows multiple advantageous characteristics that have led to an increase in the use of this species in studies modeling human medical issues, including neurobehavioral (dys)functions. For example, the cerebral cortex of pigs, unlike that of mice or rats, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 125 publications
0
68
0
3
Order By: Relevance
“…[4][5][6] This also makes piglets particularly well suited to studies of pediatric populations, and the immature piglet model of TBI has been shown to have many similar findings observed in infant TBI. 17,22 Furthermore, this infant piglet model exhibits an injury pattern and severity that is dependent upon rotational plane, similar to experimental and finite element findings in primates and humans.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[4][5][6] This also makes piglets particularly well suited to studies of pediatric populations, and the immature piglet model of TBI has been shown to have many similar findings observed in infant TBI. 17,22 Furthermore, this infant piglet model exhibits an injury pattern and severity that is dependent upon rotational plane, similar to experimental and finite element findings in primates and humans.…”
Section: Discussionmentioning
confidence: 96%
“…12,[14][15][16] Unfortunately, there is a paucity of validated behavioral tests for the immature piglet model, and those used on rodents do not translate well to pigs because of their different motor abilities, handling needs, and responses to stimuli (e.g., the well-known aversion of mice to light and open spaces is not observed in pigs). [4][5][6]23 As more robust and refined behavioral tests are developed for the porcine TBI model, it will be …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of a neonatal piglet TBI model has increased due to their similarities in human myelin sheath, tissue morphology, cerebral structure, and development [8]. Neonatal piglet TBI research allows for future research in behavioral and cognitive assessment and is presumed to be utilized as a tool for preventing secondary injury, such as stroke and resuscitation strategies [9].…”
Section: Current Modelsmentioning
confidence: 99%
“…[9][10][11] An immature porcine model is growing in prevalence as a tool in brain injury research because its tissue composition, gyrencephalic structure, and developmental growth and myelination resemble an immature human brain. [12][13][14][15][16][17][18][19] There are limited porcine behavioral and motor outcome measures, however, and few have been correlated with lesion volume from TBI.…”
Section: Introductionmentioning
confidence: 99%